A stable and practical etoposide-containing intravenous long-/medium-chain triglycerides-based lipid emulsion formulation: pharmacokinetics, biodistribution, toxicity, and antitumor efficacy. (May 2013) - Dong, Wenna; Zhang, Luna; Niu, Yantao; Fan, Dongjiao; Wu, Xiaorong; Tang, Xing; Cai, Cuifang
<x xml:space="preserve">Abstract</x> Objectives: This work aimed to evaluate pharmacokinetics, biodistribution, toxicity, and antitumor activities of a highly stable long-/medium-chain triglycerides (LCT/MCT)-based etoposide parenteral emulsion (EPE) in comparison to etoposide parenteral solution (EPS). Methods: Using high-pressure homogenization method, EPE was prepared and sterilized at 121°C for 10 min by autoclaving. The biological samples were analyzed using the UPLC-ESI-MS/MS method. Results: Superior stability of EPE was verified with no significant changes in physicochemical properties in the accelerating and long-term stability tests. Similar pharmacokinetic behavior in beagle dogs was obtained and the AUC0 – 12h values were 1196.73 ± 320.85 and 1505.56 ± 617.93 µg·h/L for EPE and EPS (p > 0.5), respectively. Likewise, no remarkable difference in biodistribution profiles in mice was found for both formulations. Safety assessment studies including hemolysis test, rabbit ear vein test and injection anaphylaxis were undertaken and the EPE was proven to be safe for intravenous administration. Specifically, after consecutive 12 weeks administration in rats, systematic and local toxicity induced by EPE were alleviated relative to that of EPS. Furthermore, significant and comparable antitumor activities to EPS were also demonstrated by EPE with tumor suppression rate (TSR) of 66.63, 55.94, and 60.16% against H460, Hep G2, and BCAP-37 human cancer cell lines in nude mice at the dose of 15 mg/kg, respectively. Conclusion: These results suggest that this LCT/MCT-based lipid emulsion is a promising alternative intravenous carrier for etoposide with high stability, improved convenience, alleviated toxicity, and noncompromised antitumor efficacy.